Histopathologic features of calcinosis cutis: a case series - Chandran, V. Anish; Sharma, Sudha; Kaushik, Rajni (International Journal of Research in Medical Sciences, 2023)
Calcinosis cutis is a rare condition characterized by the abnormal deposition of calcium salts in the skin and subcutaneous tissues. It usually occurs as an isolated entity, but is also associated with various systemic disorders. We had reported 8 cases in our department in the past one year. A striking finding was that all of them had clinical symptoms of at least 6 months and had normal serum calcium levels. The gross evaluation of the specimen showed areas of calcification which pointed out towards the diagnosis to be consistent with calcinosis cutis. The various histologic findings were presence of basophilic acellular material corresponding to calcification, eosinophilic hyalinization, foreign body giant cell reaction and an Inflammatory infiltrate. All the biopsies had conclusive evidence of the first finding. It is evident that all the cases encompass a variety of morphological findings and aim to convey a clear histopathological understanding of the lesion for a prompt diagnosis.